53BP1 regulates p53-E2F7-dependent transcriptional gene repression and participates in the Fanconi anemia pathway - Yundong Fu; Wei Wu; Maosha Zhang; Zeming Rong; Bao Lin; Xin Zhou; Dingwei Li; Xin Shi; Jing Guo; Shuyun Ma; Qiang Chen (Cell Reports)
Summary: p53-binding protein 1 (53BP1) participates in DNA damage repair through H4K20 di-methylation (H4K20me2)-mediated accumulation at DNA damage sites. However, it remains unclear whether H4K20me2-mediated 53BP1 chromatin binding regulates gene transcription in unstressed cells. Here, we demonstrate that 53BP1 depletion leads to a p53-dependent upregulation of E2F7. The direct interaction between 53BP1 and p53 is dispensable for this process, which is distinct from the established function of 53BP1-USP28-p53 complex. Notably, 53BP1 binds to E2F7 transcription start sites (TSSs) in an H4K20me2-dependent manner, which modulates p53’s binding ability through regulating epigenetic modifications at E2F7 TSS. Furthermore, our findings indicate that 53BP1 depletion represses the expression of E2F7 target genes, particularly genes involved in Fanconi anemia pathway (FA pathway), leading to cellular hypersensitivity to interstrand DNA crosslinks (ICLs). In summary, we identify 53BP1 as a negative regulator of p53-E2F7 axis, influencing the FA pathway through H4K20me2-mediated binding at E2F7 TSS.